Quantitative multiplexed elemental (C, H, N and S) detection in complex mixtures using gas chromatography. Issue 19 (10th February 2020) - Freije-Carrelo, Laura; García-Bellido, Javier; Alonso Sobrado, Laura; Moldovan, Mariella; Bouyssiere, Brice; Giusti, Pierre; Encinar, Jorge Ruiz
Abstract : Capabilities of well-established GC detectors (FID, NCD, SCD, MSD) are integrated in one single instrumental set-up able to provide simultaneous universal and H-, N- and S-element selective detection, equimolar response and structural elucidation. Abstract : We present a novel and single detection approach that enables sensitive, accurate and compound-independent quantification of N, S and H in the individual compounds present in complex samples. Integration of the whole chromatographic profile gives the total content of the elements. Simultaneous universal detection is also achieved using the C profile.